Alonso, Diego. José Enrique Rodó: una retórica de la democracia. Montevideo: Trilce, 2009, 197 p. - Olalla, Marcos (2010)
Fil: Olalla, Marcos. Consejo Nacional de Investigaciones Científicas y Técnicas